Second Broods In Bobwhite Quail - Jack A. Stanford (National Quail Symposium Proceedings, 2017)
Data on second broods in bobwhite quail is limited due to a lack of information on molting patterns, quiescence of female gonads, nesting chronology, and parental behavior in males and females. An analysis of these factors is presented along with a discussion of 19 occurrences of second-clutches in Missouri. The impact of second broods on quail populations is discussed.